Efectos del gametocida FW 450 (∞ -b-Dicloroisobutirato de Na) sobre el crecimiento y fertilidad en soja (Glicine max L.) - Lucanus de Sacks, R.; Rosas, G. S. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
This paper is a report on studies with gametocide F.W. 450 used to induce alteration in the viability of pollen of two soybeans varieties (medium early F.A.V. 24-3 and medium late Hill) at the Agricultural Experiment Station, Pergamino, Argentina, during the summer of 1962-63 The gametocide induced a general delaying of growth (flowering and maturity of pods and seed) its severity increasing when the applications were at the earlier stages of the plant growth. The flowers developed in dense racimes around the principal stem, some of which resulted abnormal with deformed pistils and indehiscent anthers The pollen viability was inversely proportional to the dose of gametocide F.W. 450, and to the age of plants at the time of sprays. The formation of pods and seeds reflected relatively the observed curves in the viability of pollen only up to the limit critical concentration of F.W. 450